Efeitos do cloridrato de isoxsuprina e da nicotina na viabilidade do retalho musculocutâneo transverso do músculo reto do abdome em ratas - Walder Costa (2014)
Introduction: The musculocutaneous flap of the rectus abdominis muscle (TRAM) is largely used for breast reconstruction, presenting significant complication rates, especially necrosis, mainly in smokers patients. Objective Analyze the effects of nicotine and of isoxsuprine hydrochloride in the musculocutaneous flap of the rectus abdominis muscle (TRAM). Method 48 Wistar rats were used, distributed into 4 groups (n=12). All the animals received the medications in the subcutaneous dorsal region, once a day, for 20 days: Group SF received saline solution; Group NI received nicotine solution; Group IS received isoxsuprine hydrochloride solution; Group NI+IS received nicotine solution + isoxsuprine hydrochloride solution. On the 21st day all the animals were anesthetized and subjected to TRAM flap delay procedure. On the second after surgery day, all the animals were anesthetized again for photographic documentation, and collection of samples for histology and euthanasia. The flaps were graphically represented in clear acetate sheets, where the contour of the flaps photos was drawn using permanent marker in brown, delimitating the areas of viability, suffering and necrosis. Such drawings were digitalized and worked in the AutoCAD program for analysis of the final area of the flap in cm2 and of the areas of viability, suffering and necrosis in cm2 and in percentage. The TRAM flap with the right and left muscles were extracted from the abdominal wall in monoblocks sectioned in the linea alba, in right and left halves. A one centimeter long segment was extracted from each side of the cranial region and from the caudal region, identified, placed in tubes with 10% formalin solution for fixation, and then processed in paraffin blocks. The histological cuts of approximately five micra were stained using hematoxylin and eosine (HE), and analyzed using light microscopy (optics). The sheets were examined by a pathologist, who ignored to which group the sample belonged. Areas of necrosis were analyzed in percentages. The data of the macroscopic analysis were analyzed according to the ANOVA test, with significance level of 5%. The SPSS 18 software was used in the comparison of the means among the four groups, in relation to the variables ± standard deviation. The data from the histological assessment were analyzed according to the Kruskal-Wallis test, with significance level of 5%. Results In the microscopic analysis of Group IS, the final area of the flap (p=0.001*) and the viable area of the flap (p=0.006*) presented the highest values in absolute numbers; the flap necrosis area (p=0.001*) presented the lowest values in absolute numbers. Groups NI and NI+IS presented, in absolute numbers, values with small differences between them, not significant for the final flap area, flap viable area, and flap necrosis area. The microscopic analysis presented non-significant results for the study of the TRAM under the action of nicotine and of isoxsuprine hydrochloride for the percentage of necrosis in the right cranial region, in the right caudal region, in the left cranial region, and in the left caudal region. Conclusions Based on this research about the viability of the TRAM flap, it can be stated that: there was no influence by the isolate use of nicotine, or in association with isoxsuprine; there was a significant improvement with the isolate use of isoxsuprine solution.